Correction: An azobenzene-modified redox-active ionic liquid electrolyte for supercapacitors. Issue 85 (11th October 2022) - Zhao, Yuhua; Chen, Yujuan; Zhuo, Kelei; Du, Quanzhou; Sun, Dong; Li, Zhiyong; Wang, Huiyong; Yan, Changling; Wang, Jianji
Abstract : Correction for 'An azobenzene-modified redox-active ionic liquid electrolyte for supercapacitors' by Yuhua Zhao et al., Chem. Commun., 2022, ; https://doi.org/10.1039/d2cc04081f .